PENGELOLAAN PROGRAM KESELAMATAN TRANSPORTASI JALAN DI JALUR PANTURA PEKALONGAN - DIO SATRIO JATI, DIO SATRIO JATI (Politika: Jurnal Ilmu Politik, 2013)
Transportation problems on roads with high density traffic, such as Jalur Pantura, areusually characterized with high numbers of accidents. Road safety problems might even becategorized as cultural matters due to its wide implications upon our daily lives. Theimplementation of road transportation safety program has become a complex issue for it isnot only related to technical challenges but also institutional, budgetary, government andsocietal supports which are closely connected to each other. Every region faces problemswith unique characteristics, therefore the way of road transportation safety program isimplemented differs according to the complexities of existing problems. This researchfindings show that the implementation of traffic safety management program within theRegency and City of Pekalongan administrative area has been fairly effective. Theconclusion is drawn upon how much the citizens regard the program as beneficial to themand how much the benefits of the program implementation are felt. Although it is impossibleto reduce the number of traffic accidents to zero, this study proves the government’s effortsto address the traffic safety issue on Pantura Route to be fairly successful.Keywords : Evaluation, Transportation Safety, Public ManagementA. PENDAHULUAN